Blood pressure in chronic kidney disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference - Cheung, Alfred K.; Chang, Tara I.; Cushman, William C.; Furth, Susan L.; Ix, Joachim H.; Pecoits-Filho, Roberto; Perkovic, Vlado; Sarnak, Mark J.; Tobe, Sheldon W.; Tomson, Charles R.V.; Cheung, Michael; Wheeler, David C.; et al. (Kidney International, 2019)
In September 2017, KDIGO (Kidney Disease: Improving Global Outcomes) convened a Controversies Conference titled Blood Pressure in Chronic Kidney Disease (CKD). The purpose of the meeting was to consider which recommendations from the 2012 KDIGO Clinical Practice Guideline for the Management of Blood Pressure in CKD should be reevaluated based on new evidence from clinical trials. Participants included a multidisciplinary panel of clinical and scientific experts. Discussions focused on the optimal means for measuring blood pressure (BP) as well as managing BP in CKD patients. Consistent with the 2012 Guideline, the conference did not address BP management in patients on maintenance dialysis.
CRIS-Team Scopus Importer:2019-05-02
Keywords: blood pressure measurement; blood pressure targets; cardiovascular events; guideline; treatment threshold